2015
DOI: 10.1515/botcro-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of Chaetoceros wighamii Brightwell (Chaetocerotaceae, Bacillariophyta) from Lake Vrana, Croatia

Abstract: -Chaetoceros wighamiiBrightwell is a planktonic diatom species originally described from brackish waters. Since its original description, the species has been reported in a wide variety of habitats, ranging from freshwater to marine. Varying descriptions exist in the taxonomic literature and several taxa have been considered as synonyms, including freshwater species Chaetoceros amanita. In this study we provide morphological and ultrastructural information on a cultured strain isolated from freshwater sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…We also suggest that cell chains of C. neogracilis , which were described for the first time in this study, might have been wrongly identified as the freshwater species Chaetoceros wighamii Brightwell (http://malina.obs-vlfr.fr; see Bosak et al. for a discussion on C. wighamii ). Similarly, the doubtful reports of C. wighamii from the Baltic Sea and Danish waters could indeed refer to C. neogracilis , as suggested by the morphological and ultrastructural similarity between Arctic strains of C. neogracilis described in this study and culture material from Danish waters attributed to C. wighamii (see fig.…”
Section: Discussionmentioning
confidence: 68%
“…We also suggest that cell chains of C. neogracilis , which were described for the first time in this study, might have been wrongly identified as the freshwater species Chaetoceros wighamii Brightwell (http://malina.obs-vlfr.fr; see Bosak et al. for a discussion on C. wighamii ). Similarly, the doubtful reports of C. wighamii from the Baltic Sea and Danish waters could indeed refer to C. neogracilis , as suggested by the morphological and ultrastructural similarity between Arctic strains of C. neogracilis described in this study and culture material from Danish waters attributed to C. wighamii (see fig.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, setae in C. wighamii are much stronger and longer and their ultrastructure very different. In C. wighamii, the setae show several rows of small poroids arranged in spiral (Bosak et al, 2015) while in C. olympicus they present a few slightly twisted rows of small rectangular poroids (Figs 30,31). Unfortunately, we have not been able to observe the ultrastructure of the valve for C. olympicus to compare it with that of C. wighamii.…”
Section: Chaetoceros Olympicusmentioning
confidence: 99%
“…The morphological features of C. olympicus and C. wighamii are summarized in Table 4. Due to its morphological similarity, the marine species C. bottnicus Cleve (and the associated species C. biconcavum Gran and C. caspicum Ostenfeld) was considered by some authors as a synonym of C. wighamii but was later reconsidered as a separate species by Sánchez Castillo et al (1992) (see Bosak et al, 2015 for further details). The resting spore of C. olympicus is different from that of C. bottnicus, whose resting spore is biconvex with spines in one or the two valves (Sánchez Castillo et al, 1992).…”
Section: Chaetoceros Olympicusmentioning
confidence: 99%
See 1 more Smart Citation